Pengaruh Ketidakjelasan Peran dan Konflik Peran terhadap Kinerja Auditor dengan Kecerdasan Emosional sebagai Variabel Moderasi: Studi Empiris Kantor Inspektorat Kota Pontianak - Itin Sumarni; Muhammad Fahmi; Rusliyawati Rusliyawati (Jurnal Simki Economic, 2024)
This research was conducted to prove the influence of role ambiguity and role conflict variables on auditor performance with emotional intelligence as a moderating variable. The samples taken were 35 Pontianak City Inspectorate auditors. Sampling using a questionnaire is distributed directly with a hard file. The data analysis used is multiple linear regression analysis with SPSS version 26 software. This research proves that the role ambiguity variable has no effect on auditor performance. The role conflict variable has a negative and significant effect on auditor performance. The emotional intelligence variable does not moderate the role ambiguity and role conflict variables on auditor performance.